Rainfall temporal variability and drought analysis by means of the Standardized Precipitation Index in Ganganagar District, Rajasthan, India - Mehta, Darshan; Caloiero, Tommaso; Yadav, Sanjaykumar; Kumar, Vikram (Frontiers in Climate, 2025)
Drought, a prolonged period of precipitation deficit, is one of the most significant hydro-meteorological hazards affecting agriculture, water resources, ecosystems, and socio-economic systems, and its impacts are becoming more pronounced under intensifying global climate extremes. This study investigates the temporal behavior and severity of droughts in the Ganganagar district of Rajasthan, India, using a 122-year record of monthly precipitation (1901-2022) analyzed through the Standardized Precipitation Index (SPI) at 3-, 6-, 9-, and 12-month timescales. Statistical techniques were employed to assess drought frequency, duration, intensity, and long-term variability, alongside evaluations of linear trends and decadal oscillations linked to large-scale monsoon dynamics. The analysis identified 46 moderate to severe drought events at the 3-month scale and 32 at the 12-month scale, with the longest drought lasting 21 months between 2000 and 2002. The frequency of extreme drought events increased notably after the 1970s, coinciding with enhanced inter-annual variability in monsoon rainfall. While the long-term linear trends in drought severity were not statistically significant, the 12-month SPI exhibited clear decadal-scale oscillations influenced by monsoon behavior, and the 3-month SPI effectively captured short-term agricultural droughts affecting seasonal crop yields. These findings provide a comprehensive understanding of drought characteristics in a highly vulnerable arid region and offer a quantitative basis for improving drought monitoring and early-warning systems. The results have direct implications for agricultural planning, irrigation scheduling, and the development of climate-informed contingency measures tailored to high-risk periods. By situating local drought assessment within the wider context of global climate extremes, this study highlights the need for integrated water resource management and region-specific policy interventions to strengthen resilience and support sustainable development in the face of an increasingly uncertain climate future.